Reconstructing Family Visitation for Incarcerated Women through Family Time: A Mubādalah-Based Model of Relational Justice in Indonesia - Hasnizam Hashim; Iffatin Nur; Sri Rahayu (Journal of Islamic Mubadalah, 2026)
This study examines the limitations of family visitation services for incarcerated women in correctional institutions in Lampung Province through the perspectives of relational justice and mubādalah. The central problem arises from the 15–30 minute visitation duration, which tends to be treated as an administrative procedure, although family visits play a crucial role in maintaining mother-child relations, marital relations, psychological stability, and readiness for social reintegration. This study aims to analyze the impact of limited visitation, explain family relations through the framework of mubādalah, and formulate a service model based on family time. The study employs a qualitative approach with an empirical juridical and multidisciplinary design. Data were obtained through in-depth interviews with 42 incarcerated women, supporting interviews with correctional officers, observation, and document study, and were analyzed using thematic analysis. The findings indicate that short visits weaken family communication, increase emotional burdens, and hinder relational recovery. This article offers a structured, just, gender-sensitive reconstruction of family time services that is relevant to the development of Islamic family law and more humane correctional policy. The article contributes by conceptualizing visitation as a space of mutuality that connects prisoners’ rights, family protection, rehabilitation, and state responsibility within Indonesia’s correctional system in a more concrete, just, measurable, and sustainable manner.